The Andean Initiative: Elevating a collaborative agenda on agrobiodiversity, climate action and healthy diets. Strategy 2020-2030 - International Potato Center (International Potato Center, 2020)
The Andes Mountains, like many parts of the world, are facing unprecedented challenges to its sustainable development in the form of the climate crisis, COVID-19 pandemic, biodiversity loss and major inefficiencies in the food system. To address these challenges, and capitalize on opportunities therein, the Andean Initiative will pursue an integrated agenda on agrobiodiversity, climate action and food for health. The Andean Initiative is a regional innovation platform aiming to facilitate collaborative science for co-innovation with emphasis on gender, indigenous people, youth, big data and digital solutions. The Initiative will contribute solutions and lessons toward sustainable mountain food systems with potential for scaling in mountain regions around the world. We envision mountains where people enjoy prosperity and well-being while conserving its rich natural resources. The Andean Initiative’s mission is to preserve the Andes’s unique agrobiodiversity and build a climate-resilient future in which all humans enjoy healthy diets.